PENGARUH LATIHAN LEMPAR TANGKAP DENGAN BOLA TERHADAP PENINGKATAN KOORDINASI MATA TANGAN PEMAIN TENNIS LAPANGAN KOTA PARIAMAN - Apri Agus; Julio Indra Fizon (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
The problem of this research is the lack of hand eye coordination of Pariaman City tennis player. So this study aims to determine the level of hand-eye coordination of tennis players Pariaman City and to find out about the effect of training with the ball throwing tehadap increasing eye-hand coordination of tennis players Pariaman field.This type of research is a quasi experiment. The population amounted to 10 sons and daughters of novice players as a sample. The sampling technique uses total sampling. The time of the research is August to September and the place is done in tennis field of Pariaman City. Hypothesis proposed that is, there is influence which means training throwing with ball to improve hand eye coordination of tennis player field of Pariaman City. Technique of data retrieval using hand eye coordination test before and after treatment practice. The collected data were tested using t-test and tested the analysis requirements. The result of hypothesis test can be concluded that